1992
DOI: 10.1159/000227097
|View full text |Cite
|
Sign up to set email alerts
|

Primary Extranodal Non-Hodgkin’s Lymphoma of the Head and Neck

Abstract: Among 387 cases of non-Hodgkin’s lymphoma (NHL) treated in our units between January 1977 and December 1990, 52 (13.4%) had primary extranodal (PE) NHL of the head and neck. The median age was 55 years with a M:F ratio of 1.9:1. The most frequent primary site was the tonsil (28 cases), followed by oral cavity, parotid gland, orbit and other sites. The aggressive histological subtypes predominate. 55.2% of the patients were in stage I and 44.8% in stage II of disease. The CR rate was high (94.2%). The 5 years’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
0
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 5 publications
7
30
0
8
Order By: Relevance
“…Among patients of DLBL subgroup, 2-year PFS and OS according to different chemotherapy regimens were MCP-842 with 51% and 69.2%, CHOP: 65% and 80%, R-CHOP: 83.3%, and 88.7% (23). Another study (14) showed that 5-year OS rate was 65% for patients. Two studies in our area showed the 3-year, 5-year and 10-year OS rates for nodal NHL patients were 65%, 54.2% and 51%, respectively (24) and for extranodal were 70%, 62.2% and 60.8%, respectively (25).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Among patients of DLBL subgroup, 2-year PFS and OS according to different chemotherapy regimens were MCP-842 with 51% and 69.2%, CHOP: 65% and 80%, R-CHOP: 83.3%, and 88.7% (23). Another study (14) showed that 5-year OS rate was 65% for patients. Two studies in our area showed the 3-year, 5-year and 10-year OS rates for nodal NHL patients were 65%, 54.2% and 51%, respectively (24) and for extranodal were 70%, 62.2% and 60.8%, respectively (25).…”
Section: Discussionmentioning
confidence: 96%
“…2017; 10(1):e5226. (14), among 387 NHL patients, the median age was 55 years with a male to female (M: F) ratio of 1.9:1. Naz et al (15) reported that in NHL patients, 67% were male and M: F ratio was 2.6:1 with the mean age of 43.9 years (range, 6 to 80 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tropism for specific sites has been particularly noticeable for the tonsils and stomach [17,18], testis and nasopharynx, and skin and bone [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for multifocal extranodal lymphomas or the preferential involvement of specific extranodal sites at recurrence remains to be investigated, but it is likely that this is closely associated with the homing process that's regulated by homing receptors, or by the lymphoid cells and ligands on the endothelial venules (10). This tropism for specific sites has been particularly noted in the tonsils and stomach, testes (11,12), and nasopharynx, in addition to the skin and bones (10,13).…”
Section: Discussionmentioning
confidence: 99%